Training practices of teachers the elementary school education in the network practice group (ppr) - Nilce Lea Lobato; Edvonete Souza; Roseli Araujo (Uni-pluriversidad, 2018)
This article is part of a larger project, “Pedagogical Practices in Networking (PPR)”, developed with the support of the Cruzeiro do Sul University, with the objective of promoting the teacher training and pedagogical professionalization based on the reflection of the inclusive educational practice. For its development, we point out the following guiding question: Are the claims being developed in the PPR project involving inclusive educational practice? The actions proposed in the scope of the PPR, which contemplates our guiding question, are based on individual and / or collective projects, called Collaborative Learning Projects (PAC), based on the student’s interest in a topic, their theoretical deepening and reflection on the practice pedagogical Thus, we used the study of case for to describe the collaborative formative practices developed between August 2017 and June 2018, organized in different formative contexts, such as: Initial Formation; Initiation to Teaching and Continuing Education. The study shows that the actions in the PPR Project suggest training possibilities to different institutional groups by allowing those involved to reflect to the action, pointing out that it is necessary to propose teacher training and that these transformations are possible.